The Transgressive Posture: Insights from Nano Discourse into the Ontology of Being a Transgressor - Lemish, Peter (Academic Quarter | Akademisk kvarter, 2011)
Considering this trajectory of the uses (or should one rather speak of the abuses?) of transgression, we can identify a number of clusters. Broadly speaking, there is a tendency to either use transgression in a socio-political context (identifying practices which move beyond the permissible or social norms), locating transgression in cultural practices (the ways we interact with the world) and finally in aesthetic practices (moving beyond the norms and conventions created by the fiction of authority). If we begin with what is maybe the broadest application of transgression as ways of overreaching taboos, we find that Peter Lemish's article The Transgressive Posture signals precisely this notion of reaching across he acceptable social boundaries — of a very sensitive field: the Israel-Arab conflict and argues that only through a transgressive posture, which Lemish develops from Heidegger, can the playing field be levelled.